2002
DOI: 10.1038/sj.bjc.6600160
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment nomogram for biochemical control after neoadjuvant androgen deprivation and radical radiotherapy for clinically localised prostate cancer

Abstract: Phase III studies have demonstrated the clinical benefit of adding neo-adjuvant androgen deprivation to radical radiotherapy for clinically localised prostate cancer. We have developed a nomogram to describe the probability of PSA control for patients treated in this way. Five hundred and seventeen men with clinically localised prostate cancer were treated with 3 -6 months of neo-adjuvant androgen deprivation and radical radiotherapy (64 Gy in 32#) between 1988 and 1998. Median presenting PSA was 20 ng ml 71 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The 5-year PSA control rates were 69 and 79%, respectively (P ¼ 0.06). This trial included patients with better prognostic features (for example, median PSA 8 ng ml À1 compared to 14 ng ml À1 in our current study) (Shipley et al, 1999;Parker et al, 2002). Subgroup analysis of the 106 men with presenting PSA levels greater than 10 ng ml À1 showed biochemical control rates of 48 and 75% (P ¼ 0.01) for the 70 and 78 Gy groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year PSA control rates were 69 and 79%, respectively (P ¼ 0.06). This trial included patients with better prognostic features (for example, median PSA 8 ng ml À1 compared to 14 ng ml À1 in our current study) (Shipley et al, 1999;Parker et al, 2002). Subgroup analysis of the 106 men with presenting PSA levels greater than 10 ng ml À1 showed biochemical control rates of 48 and 75% (P ¼ 0.01) for the 70 and 78 Gy groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, contemporary surgical series from tertiary centres have identified that up to 13% of men will have high‐grade disease [2]. In published UK and USA EBRT series, high‐risk disease has been reported in 17–19% of men [3,4]. In our own institution a recent review identified 10% of men treated by RP and 16% of men treated by EBRT have high‐risk disease ([5] and unpublished data).…”
Section: Introductionmentioning
confidence: 97%
“…Nomograms addressing biochemical and/or survival outcomes in prostate cancer have been published for patients receiving EBRT alone [ 4 - 5 , 7 , 10 - 17 ], one of RP or EBRT [ 18 - 20 ], RP or RP followed by salvage EBRT [ 21 - 28 ], and for LDR brachytherapy or LDR brachytherapy followed by EBRT [ 29 - 31 ], each reporting variable rates of ADT utilization. Similarly, the majority of published nomograms incorporate the same set of three key prognostic factors as reported in risk stratification systems (pre-treatment PSA, T stage and Gleason score), with some exceptions in studies reporting on RP or EBRT alone [ 10 , 18 ] or RP with EBRT salvage [ 21 , 23 - 28 ].…”
Section: Introductionmentioning
confidence: 99%